2020
DOI: 10.1016/j.heliyon.2020.e05746
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of plants used by the traditional healers to treat malaria in Mogovolas district, northern Mozambique

Abstract: Introduction Malaria is an important parasitic disease that affects mostly the African continent. Traditional medicine is very important in Mozambique and traditional healers play a key role in the primary health care services, particularly in rural areas. We aim to report the results of an ethnobotanical survey undertaken in Mogovolas district, northern region of Mozambique. We recorded and identified the medicinal plants used by traditional healers for treatment of malaria, as well as the mode o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 74 publications
(64 reference statements)
2
3
0
Order By: Relevance
“…With respect to Informant Factor consensus (IFC), the highest level of consensus was observed in the category of digestive system diseases (diarrhea, roundworms) (0.83), despite the category containing the lowest number of species and reported uses. Similar results have been reported in several studies where the highest level of IFC was observed in the category with the lowest number of species and reported uses [17,29,39]. The category of nervous system disorders, which includes epilepsy showed an IFC of 0.52.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…With respect to Informant Factor consensus (IFC), the highest level of consensus was observed in the category of digestive system diseases (diarrhea, roundworms) (0.83), despite the category containing the lowest number of species and reported uses. Similar results have been reported in several studies where the highest level of IFC was observed in the category with the lowest number of species and reported uses [17,29,39]. The category of nervous system disorders, which includes epilepsy showed an IFC of 0.52.…”
Section: Discussionsupporting
confidence: 90%
“…The category of nervous system disorders, which includes epilepsy showed an IFC of 0.52. This reinforces the fact that different types of plants were cited by traditional medicine practitioners for the treatment of epilepsy [29].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Successively, we included taxa described in Mozambique from the following relevant databases of plant diversity and taxonomic research: Global Biodiversity Information Facility (GBIF, https://doi.org/10.15468/dl.gq7jnb , n = 91,832 records), Plants of World Online (POWO, http://www.plantsoftheworldonline.org/ n = 5,639 species), Flora of Mozambique ( https://www.mozambiqueflora.com/ , n = 6,264 species), Flora Zambesiaca ( http://apps.kew.org/efloras/advsearch.do?reset=true , n = 4,482 species), and JSTOR – Global Plants ( https://plants.jstor.org/ , n = 1,846 species). Finally, additional taxa were found through the review of previous studies on Mozambique’s flora ( de Koning 1993 ; Timberlake et al 2007 , 2009 ; Wursten et al 2017; Bayliss et al 2010 ; Müller et al 2012 ; Burrows et al 2018 ; Darbyshire et al 2019 , n = 4,468 species) and through an extensive review of the most relevant ethnobotanical studies ( Krog et al 2006 ; Bandeira et al 2007 , 2011 ; Ribeiro et al 2010 ; Silva et al 2011 ; Williams et al 2011 ; Bruschi et al 2011 , 2014 ; Conde et al 2014 ; Santo-António and Goulão 2015 ; Moura et al 2018 ; Barbosa et al 2020 ; Manuel et al 2020 , n = 394) to document the traditional knowledge associated with the use of plants in the country.…”
Section: Methodsmentioning
confidence: 99%
“…Oladele et al (2020) conducted a systematic review focusing on curative potential on Nigeria based medicinal plant to treat and battle against COVID-19 pandemic, this study focus attention on the importance of finding out possible substitute to treat COVID-19 through natural sources, this study discusses the antiviral properties of phytochemical properties found in medicinal plant and their potential to treat the effect of COVID-19 [118] . Manuel et al conducted ethnobotanical study in Mogovolas district in Northern Mozambique and this study was executed in 14 villages where 16 traditional healers were included, study recorded total 37 plants belonging with 22 families for the treatment of malaria fever and this study highlighted importance of traditional medicine in primary health care and also further pharmacological studies on these identified medicinal plants for antimalarial activities is suggested [119] . Adi-Darko et al (2021) conducted study a laboratory based study in Ghana, where MA001 is used to treat typhoid fever, MA001 formulated from various medicinal plants and the study suggested that the formulated solid dosage forms of MA001 have the potential to improve taste, stability and compliance in the treatment of typhoid fever infection [120] .…”
Section: Cassia Alata Leavesmentioning
confidence: 99%